Multi-Omics Exploration of Obesity Biomarkers in Sedentary and Weight Loss Cohorts - Hui Wang; Yixiao Zhuang; Rong Hua; Ting Yao; Kaiqing Lin; Yitao Zhang; Rui Huang; Ruwen Wang; Shanshan Guo; Qiwei Shen; Yikai Shao; Wei Wu; et al. (Phenomics, 2025)

Associations of Plasma Lipidomic Profiles with Uric Acid and Hyperuricemia Risk in Middle-Aged and Elderly Chinese - Wanhui Kang; Xinming Xu; Xiaowei Yang; Qingqing Wu; Shuning Li; Keran Gao; Rong Zeng; Liang Sun; Xu Lin (Phenomics, 2024)
Little is known about the links of disturbed lipid metabolism with hyperuricemia (HUA). We aimed to investigate the associations of lipidomic profiles with uric acid (UA)/HUA and their modifying factors in middle-aged and elderly Chinese. A total of 350 lipids were quantified in 2247 community-based Chinese aged 50–70 years by high-coverage targeted lipidomics. HUA was defined by plasma UA > 420 μmol/L in men or > 360 μmol/L in women. The prevalence of HUA in this population was 10.4%. After multivariable adjustment including BMI and lifestyle, 123 lipids were significantly associated with UA, predominantly glycerolipids (GLs) and glycerophospholipids (GPs). Specifically, diacylglycerol [DAG (16:0/22:5), DAG (16:0/22:6), DAG (18:1/20:5), DAG (18:1/22:6)], phosphatidylcholine [PC (16:0/20:5)), and triacylglycerol (TAG (53:0)] were the most significant lipid signatures positively associated with HUA risk, while lysophosphatidylcholine (LPC (20:2)) was inversely associated with HUA risk ( p < 0.05). Network analysis also showed a positive association between TAGs/PCs/DAGs contained module and HUA risk ( p < 0.01). Notably, HUA-related lipids were associated with de novo lipogenesis fatty acids, especially 16:1n-7 (Spearman correlation coefficients = 0.32–0.41, p < 0.001). Reduced rank regression showed that increased aquatic products intake was correlated to elevated HUA risk and HUA-associated lipids; while high dairy consumption was correlated with low level of HUA-associated lipids (|factor loadings| ≥ 0.2). Moreover, mediation analyses suggested that the lipid-HUA associations were partially mediated by retinol-binding protein 4 (RBP4, mediation proportion 5–14%), an adipokine linked with dyslipidemia and insulin resistance. In conclusion, disturbed specific metabolisms of GLs and GPs were associated with high prevalent HUA, partially mediated by RBP4 and/or influenced by certain dietary factors.

Plasma Lipidomic Subclasses and Risk of Hypertension in Middle-Aged and Elderly Chinese - Zhenhua Niu; Qingqing Wu; Yaogan Luo; Di Wang; He Zheng; Yanpu Wu; Xiaowei Yang; Rong Zeng; Liang Sun; Xu Lin (Phenomics, 2022)